African migration in its national and global context - (:unkn) unknown (My University, 2012)
The chapter examines the global and national context of African migration, starting with an historical background concerning migration in sub-Sharan Africa. It describes the different routes to Europe by land and by sea. It then analyses the particularities encountered by the sub-Saharan migrants within the three countries under study _France,Britain and South-Africa.
Keywords: African Research